History by Algorithms AI and the Future of Historical Research - Lotker, Zvi 1968- (Mathematics and Statistics Series, 2025)
This book offers a first step towards getting machines to understand history in terms of analysing historical narratives.It uses computational intelligence and history texts as keys to ask different questions than have been asked about our human history so far.The book is divided into three main parts.